Definisi Sistem Portal Pengetahuan dalam Pemerintahan berdasarkan Pendekatan Modifikasi Soft System Methodology dan Hermeneutic - Satria, Wahyu Indra; Hermawan, Yanto Hermawan; Akbar, M Figo Haffidz (Jurnal Informatika Kesatuan, 2021)
A state government can implement a knowledge portal-based e-government system to properly accommodate knowledge management activities. This is also useful to minimize knowledge gaps, loss of knowledge, and waste of knowledge in the operational process of government when providing services to the community. This is intended so that the government can be massive, effective and efficient in providing public public services. The research hypothesis is that the existence of a knowledge portal-based e-Government system can assist the government in carrying out knowledge management activities in every operational activity with the aim of helping to run public service activities more effectively and efficiently. Referring to this explanation, the focus of the research carried out is to discuss and find a formal, structured scientific definition of the knowledge portal system in government based on a modified soft system methodology and hermeneutics approach. The object of research will be carried out at government agencies of the State of Indonesia with the hope of fulfilling the research objectives, namely finding a structured formal scientific definition of a knowledge portal system within a government.